2013
DOI: 10.5598/imafungus.2013.04.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Theissenia reconsidered, including molecular phylogeny of the type species T. pyrenocrata and a new genus Durotheca (Xylariaceae, Ascomycota)

Abstract: The genus Durotheca is introduced with D. depressa sp. nov., as type. Hypoxylon comedens is transferred to Durotheca, based on its morphology with further evidence from molecular phylogenetic studies; a combined β-tubulin and α-actin gene dataset. Theissenia cinerea is synonymized with D. comedens, and the type of Theissenia, T. pyrenocrata, is shown to occupy a basal, rather distant position in a monotypic clade in relation to sequenced taxa of Durotheca. This clade has an unresolved position in relation to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…The phylogeny based on BTUB showed longer distances between species and higher support values. This locus was the most informative of the three gene regions studied, which is in agreement with previous studies in other xylariaceous genera ( Hsieh et al 2005 , Læssøe et al 2013 ). After this revision Microdochium s.str.…”
Section: Discussionsupporting
confidence: 91%
“…The phylogeny based on BTUB showed longer distances between species and higher support values. This locus was the most informative of the three gene regions studied, which is in agreement with previous studies in other xylariaceous genera ( Hsieh et al 2005 , Læssøe et al 2013 ). After this revision Microdochium s.str.…”
Section: Discussionsupporting
confidence: 91%
“…However, the molecular phylogenetic data generated from the original sporothriolide producer strain clearly revealed it to belong to the Hypocreales. Aside from the above cited papers on hypoxyloid genera, even the strains obtained by Bills et al ( 2012 ), Fournier, Köpcke, et al ( 2010 ), Fournier, Stadler et al ( 2010 ), Fournier et al ( 2011 ), Læssøe et al ( 2013 ), Persoh et al ( 2009 ) were all checked for antifungal effects and by chemotaxonomic methodology, but no sporothriolide was detected by HPLC–MS and prominent antifungal effects of the Xylaria sp. studied were always due to the overproduction of cytochalasins and other compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The anamorph of D. comedens was described by Ju et al (2003) to be nodulisporium-like, but they observed rather long slender conidia that are somewhat reminiscent of scolecospores. Interestingly, the stromata of Durotheca comedens were found to contain lepraric acids, which is indicative of chemotaxonomic affinities t o Chlorostroma and Hypoxylon aeruginosum (Laessøe et al (2013 Note: The phylogenetic position of the type species of this monotypic genus is close to that of Pyriformiascoma. It has typical xylarioid ascospores and its asci are lacking an amyloid apical apparatus, but no anamorphic structures were observed (Dai et al 2016).…”
mentioning
confidence: 95%
“…Notes: This genus appears heterogeneous even after the segregation of Durotheca by Laessøe et al (2013) with respect to both teleomorph and anamorph morphology. The phylogeny of Ju et al (2007) based on protein coding genes suggests affinities to both Biscogniauxia (Graphostromataceae) and Whalleya (Lopadostomataceae).…”
mentioning
confidence: 99%